Relative accessibility analysis for key land uses: A spatial equity perspective - Kelobonye, K.; McCarney, G.; Xia, Jianhong (Cecilia); Swapan, M.; Mao, F.; Zhou, H. (Elsevier, 2019)
There is an on-going interest in measuring land use accessibility in urban areas. The transport geography and land use planning literature often tend to focus on job accessibility, and by a specific (usually motorised) travel mode, with little effort being made towards understanding the accessibility of other key destinations and their spatial equity within the urban structure. Furthermore, a lot of these studies use complex measures that are difficult to interpret and incorporate into planning and transport policies. This study employs a simple but powerful, policy friendly ‘accessible-opportunities’ approach to examine the relative accessibility and spatial equity of five key urban land uses in Perth, Australia. Comparisons are drawn between the accessibility of different land uses, as well as between access by private car and public transport, the two major travel modes in the Perth metropolitan region. The results show that jobs have the highest accessibility compared to other destination types, but poor spatial equity as outer suburbs are very poorly served (low/no job accessibility). Primary & secondary education and shopping are the most spatially equitable destinations. The results also highlight the poor accessibility provided by public transport and its inability to compete with the private car regardless of the trip purpose. Generally, the outer suburbs are under-served as services are concentrated in inner city areas. Given that more new developments have occurred in fringe areas than inner areas in recent years, increasingly more people are being disadvantaged.